Antiviral therapy for respiratory viral infections in immunocompromised patients. Issue 4 (3rd April 2017) - Shahani, Lokesh; Ariza-Heredia, Ella J.; Chemaly, Roy F.
ABSTRACT: Introduction : Respiratory viruses (influenza, parainfluenza, respiratory syncytial virus, coronavirus, human metapneumovirus, and rhinovirus) represent the most common causes of respiratory viral infections in immunocompromised patients. Also, these infections may be more severe in immunocompromised patients than in the general population. Early diagnosis and treatment of viral infections continue to be of paramount importance in immunocompromised patients; because once viral replication and invasive infections are evident, prognosis can be grave. Areas covered : The purpose of this review is to provide an overview of the main antiviral agents used for the treatment of respiratory viral infections in immunocompromised patients and review of the new agents in the pipeline. Expert commentary : Over the past decade, important diagnostic advances, specifically, the use of rapid molecular testing has helped close the gap between clinical scenarios and pathogen identification and enhanced early diagnosis of viral infections and understanding of the role of prolonged shedding and viral loads. Advancements in novel antiviral therapeutics with high resistance thresholds and effective immunization for preventable infections in immunocompromised patients are needed.